Prevalence and Risk Factors of Caprine Gastrointestinal Parasites in and around Rewa, Madhya Pradesh, India - Maravi, Durpat S.; Dixit, Pooja; Dixit, Alok K. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Prevalence studies are important for the control of parasitic diseases. A total of 1003 fecal samples of goats in and around Rewa were screened with standard flotation and sedimentation methods. The overall prevalence of gastrointestinal parasites was 92.52% in goats. The maximum prevalence of strongyles was 92.22% followed by coccidia (27.22%), Trichuris spp. (13.06%) and Moniezia spp. (7.78%). The prevalence was significantly higher (p <0.05) in the kids (96.39%) as compared to that of adults (91.59%). The prevalence of gastrointestinal parasites was non-significantly higher in males (93.97%) than that of females (91.69%). Season-wise prevalence was highest in monsoon season (95.65%) followed by that of post-monsoon season (95.41%), winter season (91.47%) and summer season (79.73%). Sex and season were the main risk factors found in the study.